한국 현대시와 숭고 - 이육사와 윤동주를 중심으로 - 이재복 (한국언어문화, 2007)
It is the Japanese colonial rule when the concept of sublime becomes controversial in earnest and appears as the one reality in the history of Korean modern poetry. It is the time when people lose their own life. It means that the period reflects existent crisis of our life. ‘Yoon Dong-Ju’ and ‘Lee Yuk-Sa’ are the poets who display this aspect of sublime deeply under Japanese colonial rule. The sublime of ‘Lee Yuk-Sa’ matters with size and height. He appeals the sublime of nation and fatherland with substance, which has height and size, such as northern district and wilderness. The height of southern district and the size of wilderness make his sublime experience remarkable originated in lost fatherland and nation and they maximizes the experience functionally. The sublime of ‘Yoon Dong-Ju’ is originated in self-reflection, and it is always concerned with enhancing transcendental consciousness. It overcomes even death, and raises degree of sublime, tracing his reason or spirit into infinite space-time. We are moved about it, experiencing the degree of sublime. His poem exists as the sublime, as it is located at the pure and high untouchable world of self-reflection. It is the reason why his poem exists, and the important position his poem occupies in the history of Korean modern poetry. Korean modern poetry and the sublime are still on the table.
Keywords: Sublime; 숭고; ideology; 이데올로기; aesthetics; 미학; positive Lust; 긍정적 쾌감; negative Lust; 부정적 쾌감; self-preservation; 자기보존; postmodernism; 포스트모더니즘